Kinerja Badan Pengelolaan Keuangan Dan Aset Daerah (BPKAD) Kabupaten Sintang - Nugroho, Fernando; Yohanes, Yulius; Arifin, Arifin (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Performance On Duty Monetary Management Earnings And Asset (BPKAD) of Local Government of Regency Sintang to management of office inventory that is in the form of: the limited human resource / of organizer of area asset of at good job unit of facet of amount and also quality so that have an effect on in management of area asset Research of concerning Performance On Duty Monetary Management Earnings and Asset of Local Government of Regency Sintang using descriptive research type by depicting fact got in research as according to what the existence of. As information source in writer take away from the officer On Duty Monetary Management Earnings and Asset of Regency Sintang specially at Asset Area consisted of by 3 section that is 1) section of Construction and planning 2) Sexy [of] penatausahaan and abolition, and 3) section of Operation and area invesment.. Data-Processing qualitative With an eye to this research 1) To measure the management of asset of Asset Area [of] [at] On Duty Monetary Management Earnings and Asset of Regency Sintang, and 2) To analyse the factors influencing performance of Asset Area of At On Duty Monetary Management Earnings and Asset of Regency Sintang From this research result there are its his weak is performance of BPKAD of Regency Sintang which do not only cause unemployed of asset owned by the local government but more than that oftentimes that matter exactly encumber the budget as well as causing budget extravagance. This is shown often the happening of inventory levying by repeatedly to result the inventory use used in is not maximal. Report administration of result of conservancy of goods of area asset from each;every unit work the Local government given by kewenangan to support the management of area asset not yet enforceable maximally is related/relevant with the difficulty to data of asset inventories which bankrupt do not From other side the factor influencing performance of officer BPKAD in management.